Lobbying expenditures on migration: a descriptive analysis - Facchini, Giovanni; Mayda, Anna Maria; Mishra, Prachi (Oxford University Press, 2015)
In this paper we carry out a descriptive analysis of lobbying expenditures on migration in the US between 1998 and 2005. While PAC contributions and lobbying are in general positively correlated, our results suggest that this is not the case when it comes to lobbying on migration. As a result, any analysis of the role of lobbying in migration should not focus on PAC contributions alone. Comparing lobbying on migration and trade, we find that substantially more resources are spent on the latter than on the former. Finally, lobbying on migration appears to be more concentrated than lobbying on trade both across sectors and across organizations.